Overhead spray water treatment as a mitigation strategy to alleviate vine stress and safeguard grape quality during heatwaves - Wilson, Alena (2024)
Changes in climate are influencing the quality of wine grapes worldwide. The impact of extremeclimate events over short periods is increasingly recognised as a serious risk to grape qualityand yield quantity. In this study, the mitigation effects of a pulsed water spray treatment on vinecanopy during heatwave (HW) events were evaluated in relation to vine condition during thegrowing season and grape quality. In the UNCuyo experimental vineyard, vines of the threecultivars Malbec (ML), Bonarda (BO) and Syrah (SY) were treated with an overhead pulsedwater spray. Heatwaves were defined as days with a minimum temperature of 21 °C and amaximum temperature of 35 °C. Two heat waves were identified during the growing season.Samples were collected at weekly intervals from veraison to harvest. On five sample dates, Leafand Stem Water Potential (LWP, SWP), Stomatal Conductance (gs), Leaf Temperature (LT),Berry Temperature (BT), Chlorophyll Content (CC), Fluorescence (Fv/Fm) and PerformanceIndex (PI) were recorded at several time points during the day to evaluate the physiologicalresponses of the vine. Berries were collected on each sample date and at harvest. Berry weight,soluble solid content and pH were recorded. In the treated vines (Trt), LWP, SWP, Fv/Fm, PI andgs were significantly higher and LT was lower than in the control vines (Ctl) during the secondheatwave, which was longer and more intense than the first one. One week after the more severeheatwave, LWP, SWP and gs remained significantly higher in Trt than in Ctl, displaying reducedphysiological stress in Trt. At harvest, the anthocyanin profile, total polyphenol index (TPI), fruityield, number of bunches and their average weight, berry weight, soluble solid content and pHwere also recorded. Bunch weight was significantly higher in Trt for all cultivars. No differenceswere found in total anthocyanin concentration. These findings indicate that the vines subjectedto targeted overhead water treatment during heatwaves underwent less physiological stress andyielded higher grape production, without increasing the risk of potential fungus diseases, in theMendoza climate. Consequently, this practice could serve as a valuable strategy for mitigatingthe adverse effects of heatwaves.